Analysis Of Tax Planning Implementation As An Effort To Reduce Corporate Income Tax - Febriyanti, Icha Bella; Rosidi (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
Abstract: This study aims to analyze the implementation of tax planning as an effort to reduce corporate income tax at PT Piranha Multi Talenta. The research was motivated by the issuance of an SP2DK notice by the tax authority on the company’s 2022 Annual Tax Return, which indicated non-compliance in managing tax obligations. This research employed a descriptive qualitative method with data collection techniques including interviews, document analysis (financial statements and tax returns), and literature review. The findings reveal that before the SP2DK issuance, tax management was primarily administrative and lacked strategic planning. After receiving the notice, the company implemented tax planning strategies by utilizing Article 23 and Article 25 tax credits and applying a gross-up policy for Article 21 income tax. These strategies effectively reduced tax liabilities, improved tax compliance during 2023–2024, minimized penalty risks, and supported financial stability.